Design and Modeling of Catamaran Flat Plate Ship with Bottom Glass Concept to Improve Tourism Underwater in Bangsring Banyuwangi - Hidayat, Ahmad; Inprasetyobudi, Hery; Darma, Yeddid Yonatan Eka (Department of Naval Architecture - Diponegoro University, 2021)
The beauty of the beach and underwater of Bangsring beach make this beach one of the leading destinations in Banyuwangi Regency. However, until today how to enjoy the beauty of the underwater can exclusively be done by diving or snorkeling, which is quite troublesome and exhausting, especially for tourists who want to enjoy and looking entertainment in a simpler way. So the concept of bottom-glass in this design is offered as a problem solving in this study, while the concept of flat plate and flat-bottom is carried out to efficiently time and cost of shipbuilding, because with this flat plate concept, there is no rolling and other material bending process. The design of the main dimensions is made based on owner requirements are obtained based on field study and literature studies, then the main parameters are obtained (LOA = 12 m, total B = 5.6 m, B each hull = 0.94 m, hull spacing = 3.72 m, T = 0.7 m, H = 1.85 m, Vs = 10 knots). To maximize the design, 4 ship models were designed with these primary parameters, based on the analysis of resistance using Maxsurf Resistance, model 4 with a maximum resistance of 4.3 kN was chosen which tend to be more effective compared with the designs of model 1, model 2, and model 3 which has a maximum resistance of 8 kN, 4.9 kN and 5.3 kN. The results of the stability analysis carried out in this design with the load case 100%, 80%, 60%, 40%, and 20%, has met all requirements for intact stability IMO MSC.36 (63) for HSC multihull Annex 7.